Symmetry : Through the Eyes of Old Masters. - Makovicky, E. (De Gruyter, 2016)
"A large range of symmetries in art is presented through clear and aesthetically outstanding examples of historical ornaments. Compendious comments illustrate the selected photographic material by addressing the interested and specialist"--